2017
DOI: 10.1111/ijfs.13459
|View full text |Cite
|
Sign up to set email alerts
|

Effect of precooking and polyphosphate treatment on the quality of catfish fillets cooked in pouch in boiling water

Abstract: Summary Cooking or reheating food in a vacuum‐sealed bag has been a common method of preparing vegetables, meats and poultry products. However, there are very few examples of vacuum‐sealed bags designed for cooking catfish fillets. The objective was to examine properties of raw frozen and precooked frozen catfish fillets that were cooked in a vacuum‐sealed pouch in boiling water. The effect of a commercial polyphosphate blend (IQF) on product properties was also evaluated. Sample analyses included weight loss,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…Li et al. () observed that IQF fish was less hard than fresh fish. The IQF catfish was markedly (Pr > F of 0.07) more intense in fibrous texture during chewing.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Li et al. () observed that IQF fish was less hard than fresh fish. The IQF catfish was markedly (Pr > F of 0.07) more intense in fibrous texture during chewing.…”
Section: Resultsmentioning
confidence: 99%
“…When the sensory firmness attribute was standardized for thickness (residual firmness), the fresh-frozen catfish fillet was significantly more firm. Li et al (2017) observed that IQF fish was less hard than fresh fish. The IQF catfish was markedly (Pr > F of 0.07) more intense in fibrous texture during chewing.…”
Section: Comparison Of Iqf Processed Catfish With Fresh-frozen Catfmentioning
confidence: 99%
See 3 more Smart Citations